Ensuring Patient Safety: The Roles of Nursing, Radiology, and Healthcare Administration - Majed Saud Tala’ Al-Mutairi1, Abdulelah Thawab Munea’a Allah Almotairi2, Amal Hussain Mahbob Almoslat3, Shadeed Marzouq Masoud Alqahtani4, Jabril Abdulaziz S Almutairi5, Mubarak Mohammed Aldosari6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Patient safety is a critical concern in healthcare worldwide, with preventable medical errors leading to significant morbidity and mortality. This paper delves into the integral roles of nursing, radiology, and healthcare administration in safeguarding patients within healthcare systems. Nurses serve as frontline advocates, radiology staff contribute to preventing diagnostic errors, and healthcare administrators oversee safety culture and policies. By fostering open communication, implementing safety initiatives, and prioritizing continuous learning, these stakeholders collectively strive to achieve zero harm in healthcare.